2010
DOI: 10.1029/2010jc006304
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial Atlantic interannual variability: Role of heat content

Abstract: [1] The dynamics of the equatorial Atlantic zonal mode are studied using observed sea surface height (SSH), sea surface temperature (SST), and heat flux and reanalysis wind stress and upper ocean temperature. Principal oscillation pattern (POP) analysis shows that the zonal mode is an oscillatory normal mode of the observed coupled system, obeying the delayed action/recharge oscillator paradigm for El Niño Southern Oscillation. Variations in equatorial averaged SSH, a proxy for upper ocean heat content, preced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 61 publications
1
45
0
2
Order By: Relevance
“…Zebiak 1993;Carton et al 1996;Ding et al 2010), we find that dynamical SST variance contributes substantially to equatorial Atlantic SST variability in boreal summer (May-July), the peak phase of the Atlantic Niño. This is in contrast to a recent study by Nnamchi et al (2015), who found that the Atlantic Niño is driven primarily by stochastic forcing.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…Zebiak 1993;Carton et al 1996;Ding et al 2010), we find that dynamical SST variance contributes substantially to equatorial Atlantic SST variability in boreal summer (May-July), the peak phase of the Atlantic Niño. This is in contrast to a recent study by Nnamchi et al (2015), who found that the Atlantic Niño is driven primarily by stochastic forcing.…”
Section: Summary and Discussionmentioning
confidence: 86%
“…Janssen et al (2008) found not only the BF, but also the recharge oscillator to be a dominant driver of TAV. Ding et al (2010) confirmed the presence of the BF with principal oscillation pattern analysis, and investigated the seasonality of the upper equatorial Atlantic (Ding et al 2009). A connection between the two modes of variability has been suggested by Foltz and McPhaden (2010), and a connection between the zonal mode and the Benguela Niño has been suggested by Lübbecke et al (2010).…”
Section: Introductionmentioning
confidence: 74%
“…Previous studies (Jansen et al, 2009;Ding et al, 2010) show that there exists some predictability in the Atlantic zonal mode. However, the major systematic errors of complex models (Davey et al, 2002;Richter and Xie, 2008;Wahl et al, 2009) in simulating the equatorial Atlantic climate need to be reduced before useful skill might be realised.…”
Section: Impact Of the Equatorial Atlantic On The El Niño Southern Osmentioning
confidence: 99%
“…The changes in the atmospheric circulation caused by ENSO affect weather around the world (e.g., Glantz et al, 1991), having large economic and social impacts. In the equatorial Atlantic, the dominant mode of interannual variability results from similar ocean-atmosphere interaction (Zebiak, 1993;Xie and Carton, 2004;Keenlyside and Latif, 2007;Jansen et al, 2009;Ding et al, 2010), and is termed the "AtImpact of the Equatorial Atlantic on the El Niño Southern Oscillation 3 lantic zonal mode" or "Atlantic Niño". However, in the Atlantic, the variability has different seasonality, and anomalous events in sea surface temperature (SST) often reach their mature phase during boreal summer (Keenlyside and Latif, 2007).…”
Section: Introductionmentioning
confidence: 99%